Behavior of unbonded flexible riser with composite armor layers under coupling loads. (1st November 2021) - Liu, Qingsheng; Xue, Hongxiang; Tang, Wenyong
Abstract: Unbonded flexible risers are widely applied in the field of ocean engineering due to their unique mechanical properties and composite materials have been introduced to reduce riser's weight. In this paper, the behavior of a typical 2.5-inch 8-layer unbonded flexible riser model with composite armor layers under coupling axisymmetric loads and bending moment is studied by theoretical and numerical methods. Firstly, considered the material and geometric properties, the bending model of composite armor layers is present according to its slipping stages; and a mathematical model that explains the effect of axisymmetric loads on the bending characteristics of unbonded flexible riser is proposed. Then, a numerical model with detailed geometric properties of unbonded flexible riser is established within ABAQUS software. After verified through experimental results by Witz (1996), the bending behavior and hysteresis phenomenon of the unbonded flexible riser with composite armor layers is conducted. Furthermore, several characteristics related to the bending properties, including external and internal pressures, axial tension, friction coefficient are discussed, and the axial and radial stress of composite tendon at different angle location is also present. The comparison results show that the effective tension would enhance the ability of unbonded flexible risers to resist bending moment. Highlights: The effect of pressure on bending properties of unbonded flexible riser is present by an analytical model. A numerical model with detailed geometric properties of unbonded flexible riser is established for verification. The bending properties and hysteresis phenomenon of unbonded flexible riser with composite armour layers are discussed. The effect of effective tension and frictional coefficient on bending properties of unbonded flexible riser is conducted. The proposed numerical model can be applied for the analysis of behavior of unbonded flexible riser under complex loads.